Perancangan Total Productive Maintenance pada PT. Formosa Ingredient Factory, Tbk. - Patrick Michaeli Antoni; Felecia Felecia (Jurnal Titra, 2022)
PT. Formosa Ingredient Factory is a company which engages in Fast Moving Consumer Goods (FMCG) with product tapioca pearl, jelly, and syrup. As company develops, PT. Formosa is able to created new plant to increase production capacity and product variation. Maintenance division at plant legok at this moment, applying corrective maintenance which is maintenance or repairing is only conducted when the machinery is broken or having a breakdown. As a result, this action created downtime on production process for waiting on the technician to make improvements. This research aim is to planning total productive maintenance at PT. Formosa Ingredient Factory. The design is using FMEA tools. Then processed data retrieved from interview with the company. From this research, the outcome is machinery identification in the form of 30 machinery in total of 80 machine, maintenance interval to make preventive maintenance schedule also creating daily checklist in total of 28 checksheet and preventive form in total of 28 form. Checksheet filling is based on SOP and work instruction which has been planned. Schedule plan and checksheet then evaluated and validated by head of factory and head of maintenance. Total Productive Maintenance (TPM) planning then implemented on legok plant.